PERBEDAAN KHASIAT ANTIBAKTERI BAHAN IRIGASI LARUTAN PROPOLIS DAN SODIUM HYPOCHLORITE TERHADAP BAKTERI Streptococcus viridans - Tabita Kusumawardhani; Sukaton Sukaton; Achmad Sudirman (Conservative Dentistry Journal, 2018)
Background. Bacteria is main etiologycal factor of pulpo-periapical disease. Therefore, eliminating bacteria is the important part on root canal treatment. It can be obtained by using irrigation agent that has antibacterial effect and endodontic sterilization agent. Beside of its antibacterial effect, the ideal irrigation agent should has an ability to remove necrotic tissue and less toxic. Propolis is well known as a natural substain that has antibacterial effect and less toxicity. So, it has a potential use as irrigation agent compared with common root canal irrigation agent, sodium hypochloryte. Purpose. The aim of this study was to observed the difference of antibacterial effect between propolis solution and sodium hypochlorite. Method. Nine samples of Streptococcus viridans were prepared and each sample devided into three parts namely group P (propolis solution), group N (sodium hypochlorite), and control group S (saline). Each group was treated with 0,01 cc agent of root canal irrigation, then was stored in incubator 370C for 24 hours. After that, inhibition zone diameter of  each group was observed.Result. The average of inhibition zone diameters in sodium hypochlorite’s group was 23,47 mm; in propolis solution’s group was 18,70 mm. There were significant difference of antibacterial effect between propolis solution and sodium hypochlorite, against Streptococcus viridans.  Conclussion. Antibacterial effect of sodium hypochlorite is higher than propolis solution, but we should consider the potential use of natural agent-propolis solution as root canal irrigation due to its antibacterial effect.